Strategi Melaksanakan Supervisi Akademik Kepala Madrasah dalam Meningkatkan Kompetensi Guru MI - Indrioko, Erwin (State Islamic Institute of Madura, 2020)
Fostering the quality and professionalism of teachers is the responsibility and obligation of the madrasah principal (supervisor) as madrasah leader. Therefore, there is a lot of work that must be done by the head of madrasah in developing teacher competence, including the head of madrasah should supervise teachers by monitoring and evaluating teacher performance so that educational goals can be met according to what is planned. The function of the head of madrasah as supervisor is very important considering that the head of the madrasah is fully responsible for the quality of madrasah learning.This research is a type of qualitative field research research. The type of research used is a case study, which is a research conducted intensively, in detail and in depth on a particular organization, institution or phenomenon. In this study, researchers conducted research at MI Miftahul Huda, having its address at Tulungagung Regency, East Java. To obtain the required data, several methods were used, namely; interviews, observation, and documentation. The data analysis stages in this study are as follows: data reduction, data presentation, and drawing conclusions.Based on the data obtained from observations, interviews and documentation, the researcher suggests several research results, namely; 1) The implementation of academic supervision at MI Miftahul Huda related to professional and pedagogical competence of teachers by the head of the madrasah is by cross-checking in the field and by regularly checking the learning tools of all teachers at the beginning of the year, such as lesson plans, syllabus, annual programs, semester programs, etc. 2) As for social competence, the head of the madrasah delivers to teachers in meetings and daily interactions in order to respect parents and guardians of students, all criticism of suggestions is accommodated and acted upon, maintaining good Javanese interaction. 3) And for the personality competence of the principal of the madrasah stick the teacher's code of ethics in the form of a banner in the teacher's room. 4)Academic supervision used at MI Miftahul Huda is a clinical supervision model.